The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1111/j.1600-0773.1981.tb03256.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Metrifonate and Dichlorvos in Plasma and Erythrocytes during Treatment of Schistosomiasis with Bilarcil®

Abstract: A method for the simultaneous quantitation of metrifonate (0,0‐dimethyl‐(1‐hydroxy‐2,2,2‐trichloroethyl)‐phosphonate) and dichlorvos (2,2‐dichlorovinyl dimethyl phosphate, DDVP) in human blood has been worked out. It is based upon multiple labelling of the compounds with deuterium and gas phase analysis using the mass spectrometer as a selective detector. The amount of DDVP in plasma is about 1% of the amount of metrifonate. In erythrocytes the corresponding amount of DDVP is 0.5% or less of metrifonate. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It is, therefore, apparent that the cholinergic mechanisms are associated with neuromuscular function~Pax et al, 1996!. Indeed, schistosomal AChE is the target for several antiparasite drugs, including hycanthon, lucanthone, metrifonate, and phosphonium compounds~Bueding et Hillman et al, 1978;Nordgren et al, 1981;Levi-Schaffer et al, 1984a;Marshall, 1987!. In an early study in our laboratory, during the isolation of the tegumental membrane of schistosomula and analysis of its major components, we observed that AChE activity was highly enriched in the isolated external membrane, ca. 350-fold as compared to the entire worm~Levi-Schaffer et al, 1984b!.…”
Section: Ache In Parasitesmentioning
confidence: 93%
“…It is, therefore, apparent that the cholinergic mechanisms are associated with neuromuscular function~Pax et al, 1996!. Indeed, schistosomal AChE is the target for several antiparasite drugs, including hycanthon, lucanthone, metrifonate, and phosphonium compounds~Bueding et Hillman et al, 1978;Nordgren et al, 1981;Levi-Schaffer et al, 1984a;Marshall, 1987!. In an early study in our laboratory, during the isolation of the tegumental membrane of schistosomula and analysis of its major components, we observed that AChE activity was highly enriched in the isolated external membrane, ca. 350-fold as compared to the entire worm~Levi-Schaffer et al, 1984b!.…”
Section: Ache In Parasitesmentioning
confidence: 93%
“…It selectively acts against the pyrophosphate binding site due to the structural mimic of anion pyrophosphate [ [105] , [106] ]. Antiparasitic drug metrifonate (Bilarcil/Memobay/ProMem®) ( 58 ) is an acetylcholinesterase inhibitor [ 107 ]. However, this drug was banned due to its high toxicity of metabolism dichlorvos in plants [ 108 ].…”
Section: Classification Of P (V)-containing Drugsmentioning
confidence: 99%
“…Although metrifonate has been on the market for more than 20 years, its pharmacological characteristics have been determined only recently. The drug is quickly absorbed in all doses between 2.5 and 15 mg/kg with no significant inter-individual variation and with no evidence of dose dependence [50,63]. Peak plasma levels are reached within 2 h and the elimination half-life is 1.7 to 2.5 h [26,41,53].…”
Section: Pharmacology and Toxicologymentioning
confidence: 99%
“…Peak plasma levels are reached within 2 h and the elimination half-life is 1.7 to 2.5 h [26,41,53]. Cholinesterase activity in plasma reaches very low levels within 15 min and remains inhibited for at least five days independent of the dose [3,63]. Even two weeks after drug intake the activity of plasma cholinesterase remained below the normal value.…”
Section: Pharmacology and Toxicologymentioning
confidence: 99%
See 1 more Smart Citation